An Empirical Study on Employee Attrition in BPO Sector (Mumbai ) - Jain, Arjita (Gyan Management Journal, 2012)
Organization’s talent is its primary source of competitive advantage in the business world. In toda highly competitive, fast changing and unpredictable business environment strategic acquisition a retention of talented workforce is a critica I and complex task for HR managers. Right ta lent acqu isitio and retention makes an organization’s strategy more strong. How to align HR with overall operatior and utilize talent in a business perspective has become a challenge for most of the business.firms; rap business growth needs to be supported by people growing at the same pace. Acquiring intel/ectua capital, developing and retaining them has become a critical task. A firm’s success depends upon n only the economic criteria but also on the capability to attract and retain intellectual capital. There are very few organizations, where problem of employee attrition is Jess or controllable. In India. the BPO sector is facing highest rate of attrition in comparison to others sectors as manufacturing te/ecom, FMCG and Financial Sectoretc. ln BPOs highest attrition is at the junior/entry level. There are l various factors that make an Entry level BPO Executive to leave one BPO and join another. Whie arc employee leaving the job is considered attrition by the one BPO, it is looked as talent acquisition by the other BPO and to the individual; it is most often means a career move, economic growth and enhancement of the quality of life. So what is a problem for one in the value chain may be an opportunity for the other BPO. Attrition rate is a burning issue for BPO HR professionals as they face tremendous problems like losing the talents and knowledge, cost related to training, recruitment etc. A creative thinking is required about the talent management challenge in the BPO sector. An indust,yspecific innovative technique has to be built by being clear about the current economy trend. The talent management practice has to remain volatile and jlexi to incorporate changes as and when demanded. This research paper is an endeavor to find out the reasons of high attrition rate in BPO sector. The sample size has been taken to be around 600 BPO employees [including entry,juniorand middle levels) from 60 Domestic and Global BPOs pertaining to Mumbai and Navi Mumbai. To achieve the objective of the study a Descriptive Research was conducted using Likert Scale and a structured questionnaire was circulated to around 600 respondents. Theda ta was collected from the respondents to know their views regarding the issues, problems and the quality of work life in BPOs. Primary sources comprise of interviews and direct responses collected through questionnaire. The secondary data has been